The Implementation of Religious Culture in Strengthening Students’ Faith Formation: An Empirical Study in Islamic Junior High School Education - Pitriani, Ratine Chantria; Amril (Journal of Religious Studies, 2025)
Purpose: This study aims to examine how the implementation of religious culture contributes to strengthening students’ faith formation in Islamic junior high school settings. Religious culture in education refers to the institutionalized practices, values, and traditions that embody spiritual and moral principles in daily school life. The research seeks to identify the extent to which these cultural practices shape students’ understanding, belief, and behavior aligned with Islamic values. Method: A quantitative descriptive design was employed involving all students of a state Islamic junior high school through a total sampling technique. Data were collected using questionnaires, interviews, and document analysis. The quantitative data were analyzed using percentage-based descriptive statistics, while qualitative insights from interviews supported contextual interpretation. Findings: The results revealed that the implementation of religious culture achieved a high level of effectiveness, with a mean score of 79.74%. Key elements supporting this success included structured morning sermons (kultum), collective worship, Qur’an recitation sessions, and teacher modeling. Two main factors were identified as dominant influencers—teacher involvement and students’ active participation. Together, these fostered a consistent integration of faith-based values in academic and social behavior. Significance: This study provides empirical evidence that embedding religious culture in Islamic education enhances students’ faith development and moral integrity. The findings highlight the strategic role of educators in cultivating spiritually grounded school environments and contribute to global discussions on faith-based character education within multicultural educational contexts.